2012
DOI: 10.1097/hjh.0b013e3283544863
|View full text |Cite
|
Sign up to set email alerts
|

A typology of neighborhoods and blood pressure in the RECORD Cohort Study

Abstract: Variations in BP were observed by levels of urbanicity and social conditions of residential neighborhoods, with different patterns for SBP and DBP. Population interventions to reduce hypertension targeted towards specific neighborhood types hold promise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
2
19
0
1
Order By: Relevance
“…As previously described in detail, the RE-CORD participants were recruited during preventive health checkups in 2007-2008 and 2011-2013, born between 1928 and 1978, and resided at baseline in 112 municipalities of the I ˘ l e-de-France Paris region (5,7,13,34). In the second wave of the study (8,26), after undergoing a medical checkup and filling computerized questionnaires at the IPC Medical Centre (10,23), 410 individuals were invited to participate in the RECORD GPS study (9), of which 247 subjects agreed to participate.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described in detail, the RE-CORD participants were recruited during preventive health checkups in 2007-2008 and 2011-2013, born between 1928 and 1978, and resided at baseline in 112 municipalities of the I ˘ l e-de-France Paris region (5,7,13,34). In the second wave of the study (8,26), after undergoing a medical checkup and filling computerized questionnaires at the IPC Medical Centre (10,23), 410 individuals were invited to participate in the RECORD GPS study (9), of which 247 subjects agreed to participate.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the association between a low social standing measurement for residential neighbourhood and blood pressure was found after adjusting for individual/neighbourhood socioeconomic status and individual risk factors for hypertension [30]. A recent systematic review revealed that the majority of studies show a reduced risk of cardiovascular disease mortality in areas having higher residential greenness [31]; a finding confirmed by another study investigating respiratory disease, which showed that children living in areas with more street trees have lower prevalence of asthma [32].…”
Section: Introductionmentioning
confidence: 99%
“…First of all, most articles are carried out exclusively in high-income countries 6 , 12 , 14 , 21 . Moreover, the focus of most publications is on adults, with a few of them analyzing together – but not stratifying by age – data from older adults.…”
Section: Introductionmentioning
confidence: 99%